2020
DOI: 10.5539/jel.v9n2p166
|View full text |Cite
|
Sign up to set email alerts
|

Nomophobia Levels and Personalities of University Students

Abstract: The development of technology has made our lives easier and has caused some dependencies to enter our lives. The aim of this study is to measure the nomophobia levels of the students at the faculty of sports at Uşak University and the faculty of technology at Isparta Applied Sciences University and to examine the relationship of personality with the level of nomophobia.The sample of the study consists of a total of 408 students at the faculty of sports at Uşak University and the faculty of technology at Ispart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
2
11
0
3
Order By: Relevance
“…The ages were similar to the studies done by Choi et al, Krajewska et al, Dixit et al 31,33,34 In the manner of the age effect, there were no significant differences in nomophobia levels, sub‐dimensions and Fagerström scores ( P > .05). Like the nomophobia scores of university students in other studies there was no significant difference about age factor 2,30,35,36 . Controversially Erdem et al, 37 found a significant relationship between age and nomophobia.…”
Section: Conclusion and Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…The ages were similar to the studies done by Choi et al, Krajewska et al, Dixit et al 31,33,34 In the manner of the age effect, there were no significant differences in nomophobia levels, sub‐dimensions and Fagerström scores ( P > .05). Like the nomophobia scores of university students in other studies there was no significant difference about age factor 2,30,35,36 . Controversially Erdem et al, 37 found a significant relationship between age and nomophobia.…”
Section: Conclusion and Discussionmentioning
confidence: 69%
“…Females had higher levels of nomophobia than men in these two sub‐dimensions. Dalbudak et al Supporting this claim 35 …”
Section: Conclusion and Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Females had higher levels of nomophobia than men in these two sub-dimensions. Dalbudak et al Supporting this claim 36 .…”
Section: Conclusion and Discussionmentioning
confidence: 91%